2016
DOI: 10.1002/mabi.201600248
|View full text |Cite
|
Sign up to set email alerts
|

Probing Endosomal Escape Using pHlexi Nanoparticles

Abstract: The effective escape of nanocarriers from endosomal compartments of the cell remains a major hurdle in nanomedicine. The endosomal escape of pH-responsive, self-assembled, dual component particles based on poly[2-(diethylamino)ethyl methacrylate)(PDEAEMA) and poly(ethylene glycol)-b-poly[2-(diethylamino)ethyl methacrylate) (PEG-b-PDEAEMA) has been recently reported. Herein, we report that polymer molecular weight (M ) can be used to tune endosomal escape of nanoparticle delivery systems. PDEAEMA of M 7 kDa, 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 39 publications
(51 reference statements)
4
55
1
Order By: Relevance
“…This suggests that release was more likely due to a membrane disrupting or pore‐forming mechanism than complete vesicle rupture. Later work showed that the endosomal escape of these pHlexi particles could be tuned by the molecular weight of the polymer building blocks . This indicates that small variations in nanoparticle properties can also play an important role in cellular behavior.…”
Section: Strategies To Engineer Endosomal Escapementioning
confidence: 99%
“…This suggests that release was more likely due to a membrane disrupting or pore‐forming mechanism than complete vesicle rupture. Later work showed that the endosomal escape of these pHlexi particles could be tuned by the molecular weight of the polymer building blocks . This indicates that small variations in nanoparticle properties can also play an important role in cellular behavior.…”
Section: Strategies To Engineer Endosomal Escapementioning
confidence: 99%
“…This was thought to be by pH-dependent membrane interaction. A major limitation of the current pH-responsive nanoparticle strategies based on membrane interaction is the size of cargo that can escape the endosome, as there are numerous reports of the escape of small cargo but limited examples of large cargo [189,190,191]. Further understanding on strategies to facilitate the endosomal escape of large material are needed to enable the efficient intracellular delivery of biological therapeutics.…”
Section: Cellular Level Interactions and Behaviorsmentioning
confidence: 99%
“…In a subsequent study, we developed a library of nanoparticles to test the effect of polymer molecular weight on membrane interaction and endosomal escape. [14] A range of PDEAEMA homopolymers were synthesised with molecular weights of 7, 27, 56 and 106 kDa using reversible addition-fragmentation chain transfer (RAFT). These polymers were combined with PEG-b-PDEAEMA of 16 kDa to form nanoparticles using nanoprecipitation.…”
Section: Investigating the Impact Of Nanoparticle Structure On Endosomentioning
confidence: 99%